Assessment of Indigenous N, P and K Supply for Rice Site Specific Nutrient Management in Buru Regency - Susanto, Andriko Noto; Sirappa, Marthen Pasang (UNIVERSITY OF LAMPUNG, 2014)
Rate of fertilizer that should be applied to rice soil based on Site Specific Nutrient Management (SSNM) depends on indigenous nutrient supply, its recovery efficiency, and the amount of nutrients requirement to achieve the yield target. Research on nutrient omission plot was conducted in farmers irrigated land on Waeapo plain, Buru Island. In this area, N, P, and K were the main limiting factors of rice growth and yield. To overcome the constraint, this assessment was conducted to determine the indigenous supply of N, P and K and optimal target of rice productivity. Results of this assessment showed that the average of rice optimum productivity (Mg grain water content/w.c. 14% ha-1) in Waeapo plain was 6.55 Mg DGM (Dry Grain Milled) ha-1, with range from 5.6 to 7.3 Mg DGM ha-1 depended on the indigenous supply of N, P and K. The average value of the indigenous N, P and K supplies in Waeapo plain Buru was 65.59 kg N ha-1, 13.70 kg P ha-1 and 78.65 kg K ha-1, respectively while average productivity of rice on that indigenous N, P and K supplies was 5.05, 5.96 and 6.05Mg DGM ha-1, respectively. The value of indigenous nutrient supply of this nutrient can be used as a basis of fertilizer recommendation with the SSNM concept. Keywords: Indigenous nutrient supply; nitrogen; phosphorus; potassium; Site Specific Nutrient Management [How to Cite: Andriko NS and MP Sirappa. 2014. Assessment of Indigenous N, P and K Supply for Rice Site Specific Nutrient Management in Buru Regency. J Trop Soils 19: 151-159. Doi: 10.5400/jts.2014.19.3.151]